Unusual CT and MR Findings of Inflammatory Pseudotumor in the Parapharyngeal Space: Case Report - Nakayama, Keiko; Inoue, Yuichi; Aiba, Tsunemasa; Kono, Kinuko; Wakasa, Kenichi; Yamada, Ryusaku (American Journal of Neuroradiology, 2001)
Summary: Unusual MR and CT findings of an inflammatory pseudotumor in the parapharyngeal space of a 73-year-old woman are reported. The mass was hypointense on T1- and T2-weighted images and demonstrated ring enhancement after contrast medium injection. Punctated calcifications were scattered at the periphery. Inflammatory pseudotumors in the parapharyngeal space are rare, and only three cases have been reported. The possible pathogenesis and varieties of inflammatory pseudotumors are discussed.